Method of structural-parametric adaptation of "smart city" to digital economy - K. A. Radkevich; S. V. Kruglikov (Informatika)
Objectives. The interaction between a "smart city" and digital economy can be explored and analyzed within the framework of the structural-parametric adaptation method. This method allows the adaptation of the parameters and structure of the system model to ensure optimal functioning in the conditions of changing external environment. The concept of a "smart city" can be examined based on the principles of structural-parametric adaptation, such as interoperability, decentralization, virtualization, real-time operation, modularity, and service orientation. Within the scope of structural-parametric analysis, a "smart city" is regarded as a complex multi-level cyber-physical system.Methods. Structural-parametric adaptation methods and structural-parametric optimization methods are employed.Results. A general form of the algorithm for structural-parametric adaptation of the system and a mathematical model of the problem of structural-parametric optimization of "smart city" systems have been developed.Conclusion. To address the challenges of constructing, optimizing, and adapting the structure of a "smart city" system, it is necessary to consider the technical requirements of the system and the capabilities of the infrastructure used, and to apply the structural-parametric adaptation method.